Pyrrhotite as a tracer for denudation of the Taiwan orogen - Chorng‐Shern Horng; Chih‐An Huh; Kuo‐Hang Chen; Chun‐Hung Lin; Kai‐Shuan Shea; Kan‐Hsi Hsiung (Geochemistry, Geophysics, Geosystems)
The use of pyrrhotite as an index mineral to delineate metamorphic isograds has long been proposed. However, details of the occurrence of pyrrhotite in different metamorphic facies and its implications have rarely been explored. Here, by simple characterization of magnetic properties and mineral identification, we demonstrate that pyrrhotite is widely distributed in low‐grade metamorphic terranes of Taiwan's Central Range and in sediments derived therefrom. By coupling the distribution of pyrrhotite in rocks with that in dated sediment strata, we have studied the denudation history of Taiwan's orogen from a source‐to‐sink perspective. We suggest that pyrrhotite is a potential tracer for studying surface processes in orogens with high denudation rates similar to that in Taiwan.